PENGARUH AKSES MEDIA SOSIAL (TIKTOK) SEBAGAI SARANA EDUKASI KESEHATAN TENTANG HIV/AIDS DI SMAN 2 KOTA PEKANBARUTAHUN 2025 - Maharani, Riri; Nuranty; Winda Septiani (HEALTH CARE: JURNAL KESEHATAN, 2025)
HIV/AIDS is a disease that compromises the immune system and continues to pose a public health challenge, particularly among adolescents. Health education through social media platforms such as TikTok offers an engaging and accessible alternative for disseminating information to younger generations. Preliminary surveys reveal that only 30% of students possess accurate foundational knowledge about HIV/AIDS, while the remaining 70% demonstrate limited or incorrect understanding. This study aims to examine the impact of accessing TikTok as a health education medium on adolescents' knowledge and attitudes toward HIV/AIDS at SMAN 2 Pekanbaru. A pre-experimental design using a One Group Pre-test and Post-test approach was employed, involving 80 eleventh-grade students selected through purposive sampling. The study was conducted at SMAN 2 Pekanbaru ty in May 2025. The independent variable was the use of TikTok for health education, while the dependent variables were students’ knowledge and attitudes regarding HIV/AIDS. Data analysis was performed using the Wilcoxon test. The results indicated a significant difference in both knowledge (p = 0.001) and attitudes (p = 0.001) before and after the intervention, with the average knowledge score increasing from 3.09 to 8.88 and the average attitude score from 51.156 to 81.156. It can be concluded that utilizing TikTok as a social media platform is effective in enhancing adolescents' knowledge and attitudes toward HIV/AIDS. It is recommended that SMAN 2 Pekanbaru and healthcare institutions leverage social media, particularly TikTok, as an innovative medium for HIV/AIDS prevention education among youth.